Glucocorticoid Signaling and the Aging Heart - Cruz-Topete, Diana; Oakley, Robert H.; Cidlowski, John A. (Frontiers in Endocrinology, 2020)
A decline in normal physiological functions characterizes the aging process. While some of these changes are benign, the decrease in the function of the cardiovascular system that occurs during aging leads to the activation of pathological processes associated with an increased risk for heart disease and its complications. Imbalances in endocrine function are also common occurrences during the aging process. Glucocorticoids are primary stress hormones and are critical regulators of energy metabolism, inflammation, and cardiac function. Glucocorticoids exert their actions by binding the glucocorticoid receptor (GR) and, in some instances, to the mineralocorticoid receptor (MR). GR and MR are members of the nuclear receptor family of ligand-activated transcription factors. There is strong evidence that imbalances in GR and MR signaling in the heart have a causal role in cardiac disease. The extent to which glucocorticoids play a role in the aging heart, however, remains unclear. This review will summarize the positive and negative direct and indirect effects of glucocorticoids on the heart and the latest molecular and physiological evidence on how alterations in glucocorticoid signaling lead to changes in cardiac structure and function. We also briefly discuss the effects of other hormones systems such as estrogens and GH/IGF-1 on different cardiovascular cells during aging. We will also review the link between imbalances in glucocorticoid levels and the molecular processes responsible for promoting cardiomyocyte dysfunction in aging. Finally, we will discuss the potential for selectively manipulating glucocorticoid signaling in cardiomyocytes, which may represent an improved therapeutic approach for preventing and treating age-related heart disease.